Growth Analysis in Moghania macrophylla (willd) O. Ktze in the Nursery - Singh, B. P.; Kumar, P. (Indian Forester, 1996)
A Field experiment was conducted at the Indian Lac Research Institute, Namkum, Ranchi duriog 1988 and 1989. The growth analysis results revealed that various parameters had more values in first phase of 60-90 days after sowing (DAS) than advanced stage of the seedling growth (90.105 DAS). Relative growth rate (RGR). Crop growth rate (CGR) and net assimilation rate (NAR) were significantly affected by different date of sowiog in nursery during both the years except in the year 1988 at 90-105 DAS. However, variation in date of sowing did not affect LAR at different periods. The result indicated the need to adopt better management practices at early growth stages for better growth and development.